Research Gap Strategies In A Rticle Introduction Section On Teaching English As Foreign Language (Tefl) In Sinta 1 Journals - Herly Fathonah Agustika; Ririn Putri Ananda (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The research gap is a situation where inconsistentcies or gaps are found between occurs due to differences in results, concepts, data and theories from research results. The objective of this study is to find out about a) what are research gap strategies used by the researcher, and b) what is dominant research gap strategies used in the article introduction section in Teaching English as Foreign Language (TEFL). This research aims to identify the research gap strategies in article intoductions section in SINTA 1 journals. The jounals were taken in (IJOLE, SIELE, TEFLIN) journals, and were analyzed on five elements of research gap strategies following Arianto et al. (2021). Therefore, future studies have to analyze more extensive samples obtained from more journals to represent the feature of the articles in the journals regarding the RG strategies. Keywords: TEFL, SINTA 1 journals, research article introduction, research gap strategies.